(untitled) (The Review of Diabetic Studies, 2025)
Background: Access to oral healthcare remains a significant challenge for rural populations due to geographical barriers, a shortage of dental professionals, and limited resources. Teledentistry offers a promising digital solution to extend dental care and improve service delivery in underserved areas. However, evidence regarding its practical application in enhancing access to care within routine rural primary healthcare workflows remains limited. Methods: This quantitative observational study employed a cross-sectional design to evaluate the role of teledentistry in a rural primary healthcare setting. Data were collected from 240 adult patient cases assessed via teledentistry and 38 healthcare providers. The intervention involved store-and-forward and synchronous consultations for preliminary assessment, triage, and referral guidance. Outcome measures included the effectiveness of remote management, referral decision accuracy, timeliness of care, and provider experiences. Results: Nearly half (43.3%) of patient cases were managed remotely without requiring an in-person referral. Dental pain was the most common presenting complaint (38.3%). Teledentistry demonstrated high referral accuracy, with 80.8% of referrals confirmed as appropriate by specialists. Only 6.7% of cases required immediate emergency referral. The majority of healthcare providers reported improved confidence in oral assessment (76.3%), faster referral decisions (81.6%), and a reduction in unnecessary referrals (71.1%). Conclusion: Teledentistry significantly improved access to oral healthcare for rural populations by enabling effective early assessment, accurate triage, and efficient referral coordination. It supported the remote management of a substantial proportion of cases and enhanced clinical decision-making. These findings advocate for the integration of teledentistry as a complementary component of rural primary healthcare services to reduce oral health disparities.